The dominance of paddy wholesalers in the paddy supply chain of Bangladesh-A case study of Habiganj district - Junayed Uddin Ahmed; Maya Sultana (Cogent Food & Agriculture)
In Bangladesh, numerous paddy traders are involved in the supply chain, with paddy wholesalers playing a dominant role. This study investigates the declining influence of local village traders and the factors contributing to this shift. Data were collected through face-to-face interviews using a semi-structured questionnaire and simple random sampling. The sample included 128 farmers, 17 paddy wholesalers, and 3 local village traders. Descriptive statistics and t-tests were employed for analysis. Results show that most farmers sell paddy to wholesalers, who are full-time traders with access to shops, storage, labour, and transport. Wholesalers also provide credit, bags, and information, making them more attractive trade partners. In contrast, non-licensed village traders are seasonal, lacking infrastructure and resources. As a result, wholesalers dominate the paddy market. However, farmers struggle to profit from paddy sales and must pursue supplementary work to sustain livelihoods. In that case, a farmers’ agriculture cooperative society or introducing a government procurement system can help reduce traders’ dominance in the paddy supply chain and help farmers get high prices for paddy.